AL amyloidosis with a localized B cell neoplasia - Stuhlmann-Laeisz, Christiane; Schönland, Stefan; Hegenbart, Ute (Virchows Archiv, 2019)
Immunoglobulin light chain-derived (AL) amyloidosis may occur as a systemic disease usually with dismal prognosis and a localized variant with favorable outcome. We report 29 patients with AL amyloidosis and associated lymphoplasmacytic infiltrate spatially related to amyloid deposits. In 17 cases, the amyloid deposits were classified as ALλ and 12 as ALκ Histopathology in all cases showed relatively sparse plasma cells and B cells without tumor or sheet formation by the lymphoplasmacytic infiltrate. The B cells predominantly showed an immunophenotype of the marginal zone. In situ, hybridization revealed 17 cases with λ− and 10 with κ light chain restricted plasma cells, which was concordant with the AL subtype in each case. Clonal immunoglobulin heavy variable gene (IGHV) or κ light chain rearrangement was found in 23/29 interpretable cases. A single case harbored a MYD88L265P-mutation. Taken together, we detected 27 (93%) cases of AL amyloidosis with an associated light chain restricted and predominantly molecularly clonal plasma cell population. Clinical data were available in 18 patients. Five patients suffered from systemic lymphoma and two from systemic AL amyloidosis. The remaining cases were classified as localized with regard to both, the AL amyloidosis and the light chain restricted plasma cell population. To the best of our knowledge, we herein present the largest cohort of AL amyloidosis associated with a light chain restricted and predominantly molecularly clonal plasma cell population, which we designate as a distinct disease entity: “AL amyloidosis with a localized B cell neoplasia of undetermined significance”.
Gesehen am 28.06.2019